Mini-incisional entropion repair for correcting involutional entropion: Full description and surgical outcome. Issue 33 (August 2019) - Han, Jisang; Lee, Shin-Hyo; Shin, Hyun Jin
Abstract : Abstract: The aim of the study was to report the surgical outcome of mini-incisional correction method to treat involutional entropion. This is a retrospective interventional case series of 46 eyelids in 31 patients with involutional entropion and significant ocular irritation. In this technique, after turning the lower eyelid inside out, threads are introduced into it through the conjunctiva close to the inferior fornix. The lower lid retractor and tarsus are then connected using threads. These threads are applied at 3 locations of the lower eyelid and tightening them results in the eyelid being everted and the correction of entropion. Surgical success was defined as no contact between the eyelashes and the globe during forced closure of the eyelids. Surgical failure was defined as persistence of the eyelashes remaining in contact with the globe or cosmetic dissatisfaction. During the mean follow-up period of 22.1 months (range, 12–34 months), 43 of the eyelids (93.5%) were successfully corrected. Two patients (3 eyelids) experienced recurrence: 1 had involutional entropion combined with a cicatricial component, and the other had blepharospasm and apraxia of eyelid opening related to Parkinsonism. No postoperative complications such as overcorrection, suture-knot exposure, or ocular irritation were observed. Our mini-incisional entropion repair is based on reinforcement of the lower eyelid retractors using transconjunctival buried sutures. This technique is a quick, simple, and predictive for involutional entropion repair, and has a high success rate. Abstract : Supplemental Digital Content is available in the text